A study of Some Hormones and Antioxidant ‎Systems Disturbances in Older Men (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Ageing is a physiological phenomenon that manifested itself with disturbances of many homeostatic regulating mechanisms of the body . The present study was conducted and employed to investigate two major systems( hormones and antioxidant systems) that can be implicated in progress of aging .The total number of subjects included in the present study was fifty (50) healthy men and classified according to their ages into two groups, the first group included 25 younger men (control group) and their ages ranged between 21 to 30 years old whereas the second group included 25 older men and their ages were between 61 to 70 years old.  Data obtained from this study indicated a significant decrease(p